2018
DOI: 10.3389/fonc.2018.00086
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 and Anti-CTLA-4 Therapies in Cancer: Mechanisms of Action, Efficacy, and Limitations

Abstract: Melanoma, a skin cancer associated with high mortality rates, is highly radio- and chemotherapy resistant but can also be very immunogenic. These circumstances have led to a recent surge in research into therapies aiming to boost anti-tumor immune responses in cancer patients. Among these immunotherapies, neutralizing antibodies targeting the immune checkpoints T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) are being hailed as particularly successful. These antibodies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
864
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,099 publications
(878 citation statements)
references
References 131 publications
(149 reference statements)
8
864
0
6
Order By: Relevance
“…65,66 In breast cancer, immunotherapy clinical trials have been mainly focused on metastatic TNBC, a genomically unstable subtype of breast cancer that is believed to be the most immunogenic. In recent years, antibodies to PD-L1, PD-1, or CTLA4 have been developed to target immune-suppressive pathways, allowing for cytotoxic T cells to infiltrate and kill tumor cells.…”
Section: Ddpcr Detection Of Esr1 Mutations In Patient Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…65,66 In breast cancer, immunotherapy clinical trials have been mainly focused on metastatic TNBC, a genomically unstable subtype of breast cancer that is believed to be the most immunogenic. In recent years, antibodies to PD-L1, PD-1, or CTLA4 have been developed to target immune-suppressive pathways, allowing for cytotoxic T cells to infiltrate and kill tumor cells.…”
Section: Ddpcr Detection Of Esr1 Mutations In Patient Biopsiesmentioning
confidence: 99%
“…In recent years, antibodies to PD-L1, PD-1, or CTLA4 have been developed to target immune-suppressive pathways, allowing for cytotoxic T cells to infiltrate and kill tumor cells. 65,66 In breast cancer, immunotherapy clinical trials have been mainly focused on metastatic TNBC, a genomically unstable subtype of breast cancer that is believed to be the most immunogenic. 67,68 The multicenter I-SPY 2, phase 2 clinical trial is evaluating novel neoadjuvant therapies and comparing immune therapy in combination with chemotherapy.…”
Section: Clinical Implications and Therapeutic Strategies To Treat Mbmentioning
confidence: 99%
“…First encouraging results have been reported, even though more trials are needed to optimize dosing, timing of mono-or combination treatment, and the feasibility of repeated treatment cycles to achieve clinical efficacy with minimal side effects. 29,30 Overall, and without a doubt, immunotherapy constitutes a breakthrough in cancer treatment with major impact on patient survival and disease outcome. As our knowledge about immune cells, their differentiation, function, and regulation increases, and novel experimental tools enable us to dissect the specifics of distinct tumor environments in different tumor types, we should be optimistic about the future and our ability to design better, more targeted, and highly efficacious cancer therapies.…”
Section: Act or Car T Cell Therapymentioning
confidence: 99%
“…). First encouraging results have been reported, even though more trials are needed to optimize dosing, timing of mono‐ or combination treatment, and the feasibility of repeated treatment cycles to achieve clinical efficacy with minimal side effects …”
mentioning
confidence: 99%
“…Treatment of cancer patients with anti-PD-1 or anti-PD-L1 has succesfully induced tumor regression in some cases. However, anti-PD-1 efficacy is variable across patients and cancer types [25]. Recently, we showed that PD-1 can also be expressed by bystander T cells in the tumors [2], making this receptor not exclusively expressed by tumor-specific cells, and raising questions about the effect of anti-PD-1 treatment on these cells.…”
Section: Expression Of Pd-1 Is Partially Absent On Ebv-specific Cd8 +mentioning
confidence: 99%